The Formula media in vitro Propagation and Conservation of Ludwigia sp. - Endang Gati Lestari; Media Fitri Isma Nugraha; Rossa Yunita (Journal of Tropical Biodiversity and Biotechnology, 2023)
The aquatic plant "Red Malang” (Ludwigia sp.) has a fairly high economic value as an ornamental aquatic plant, so it has the potential to be developed. The growth of in vitro cultures in culture bottles is high-speed, so it is necessary to find a formula media to inhibit growth so that the frequency of subcultures is reduced. The current research aims to produce a formula media for shoot multiplication and in vitro culture conservation. The research was carried out at the ICABIOGRAD tissue culture laboratory from April 2020 to June 2021. Research activities included plant propagation, conservation, and regeneration after conservation. Plant material was using in the form of a culture collection in the ICABIOGRAD tissue culture laboratory, treatment media for propagation were BA (0; 0.1; 0.3; 0.5; 0.7 and 0.9 mg/L) + thidiazuron (TDZ) (0 and 0.1mg/L). For conservation were MS + BA medium (0 and 0.1 mg/L) + paclobutrazol (0; 0.1; 0.3; 0.5; 0.7 mg/L) and for shoot regeneration after conservation using MS medium without Plant Growth Regulator (PGR). Data analysis using the Anova SAS version 9.0 test program. Further test using DMRT test with alpha level 5%. There was no difference in the mean value between levels of TDZ treatment on the number of shoots and leaves. The difference in the mean value between levels of TDZ treatment was very significant on shoot height, the number of roots, and root length. BA treatment with a concentration of 0.7 mg/L is better because it gives higher results for each observation variable. For conservation, treatment with paclobutrazol 0.5 mg/L inhibited shoot and leaf count, and 0.3 mg/L inhibited shoot formation. Cultures stored for six months grew normally after being regenerated. The highest shoots and the highest number of leaves were obtained from the treatment of paclobutrazol without BA. This study indicated that the propagation media of aquatic plants Ludwigia sp. did not require high concentrations of BA. Cultures could be stored for over six months using paclobutrazol with 0.3-0.6 mg/L.